Coupling particle scale model and SuperDEM‐CFD for multiscale simulation of biomass pyrolysis in a packed bed pyrolyzer. Issue 4 (7th January 2021) - Gao, Xi; Yu, Jia; Lu, Liqiang; Rogers, William A.
Abstract: An efficient biomass pyrolysis process requires a comprehensive understanding of the chemical and physical phenomena that occur at multi‐length and time scales. In this study, a multiscale computational approach was developed and validated for biomass pyrolysis in a packed‐bed reactor by integrating pyrolysis kinetics, a particle scale model, and Superquadric Discrete Element Method‐Computational Fluid Dynamics (SuperDEM‐CFD) in open‐source code MFiX. A one‐dimensional particle–scale model that discretizes the characteristic length of biomass particle into layers was developed to predict the intraparticle phenomena inside a single particle. The 1D model was validated by comparing it with a single biomass particle pyrolysis experiment. A recently developed SuperDEM‐CFD model was employed to simulate the non‐spherical particle–particle contact and fluid‐particle interaction. The coupled model was applied to simulate the pyrolysis of cubic biomass particles in a packed bed and validated by comparing with experimental data. Simulation with and without particle–scale model was compared, and the effect of the gas–solid heat transfer models was also investigated.